2013
DOI: 10.14434/josotl.v14i1.3649
|View full text |Cite
|
Sign up to set email alerts
|

Interteaching: Its effects on exam scores in a compressed-schedule format

Abstract: Although previous research has found interteaching to be an effective form of instruction, all of the currently published data have been collected in courses that have allowed for a minimum of 48 hours between class sessions. In the current study, we examined the effectiveness of interteaching compared to traditional lecture during a six week summer session of a behavior modification course. Two non-concurrent sections of the behavior modification course were taught during which the instructor alternated betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 24 publications
(44 reference statements)
0
21
0
Order By: Relevance
“…The present study was a systematic replication of Zayac and Paulk (2014) and aimed to compare IT to a lecture condition that allowed students access to prep guide questions to use as an optional study guide. This study evaluated the effects of IT, ST (i.e., lecture only), and STϩ in an online asynchronous learning environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study was a systematic replication of Zayac and Paulk (2014) and aimed to compare IT to a lecture condition that allowed students access to prep guide questions to use as an optional study guide. This study evaluated the effects of IT, ST (i.e., lecture only), and STϩ in an online asynchronous learning environment.…”
Section: Discussionmentioning
confidence: 99%
“…The primary aim of this study was to further investigate the efficacy of IT in comparison to lecture conditions that include additional components (i.e., optional study guides) that may also improve student learning outcomes. To do this, we systematically replicated Zayac and Paulk (2014) by comparing IT to a lecture condition that allowed students access to an optional study guide in a compressed schedule, but set the class up so that IT assignments occurred only once per week instead of on 4 days per week. In Zayac and Paulk's lecture condition, students had access to study guides that were brief and less detailed than the prep guides in their IT condition.…”
mentioning
confidence: 99%
“…For example, Saville and colleagues (2006) asked students to complete a two-item questionnaire at the end of the semester that asked which of the two teaching methods they preferred, and to rate their extent of learning from each method. Zayak and Paulk (2014) had a similar approach to evaluate social validity, but included additional open-ended questions in the form completed by participants. The reported preference for interteaching when compared to lecture has been mixed, with at least some studies reporting student preference for interteaching while others reported preference for lecture even when interteaching was more effective (see Querol, Rosales, & Soldner, 2015 for a review of empirical research on Interteaching including the use of social validity measures).…”
mentioning
confidence: 99%
“…Lastly, contingency on discussion or prep guide completion was associated with the effectiveness of interteaching ( p < .05). Studies in which no contingencies were implemented (e.g., Edwards, 2005 ; Saville et al, 2014 ; Saville et al, 2005 ; Scoboria & Pascual-Leone, 2009 ; Slezak & Faas, 2017 ) had larger effect sizes than those that had contingencies in place (Anbro, 2015 ; Cezeaux & Keyser, 2018 ; Felderman, 2016 ; Rieken et al, 2018 ; Soldner et al, 2015 ; Zayac & Paulk, 2014 ). However, these findings should be interpreted carefully because a closer inspection of the records related to this regression showed that one of them reported a somewhat disproportionate effect size (Saville et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%